Spatially confined synthesis of vanadium nitride nanodots intercalated carbon nanosheets with ultrahigh volumetric capacitance and long life for flexible supercapacitors. (September 2018) - Li, Qingwei; Chen, Ye; Zhang, Jiabao; Tian, Weifeng; Wang, Lei; Ren, Zhiguo; Ren, Xiaochuan; Li, Xingxing; Gao, Biao; Peng, Xiang; Chu, Paul K.; Huo, Kaifu
Abstract: High volumetric capacitance electrode materials are highly desirable for miniaturized and portable capacitive storage devices. Herein, a spatially confined strategy to prepare 0D-in-2D pillared lamellar hybrid comprising vanadium nitride nanodots intercalated carbon nanosheets (VNNDs/CNSs) is proposed for promising capacitive material with high volumetric capacitance. The VNNDs/CNSs shows an ultrahigh volumetric capacitance of 1203.6 F cm −3 at 1.1 A cm −3 and rate capability of 703.1 F cm −3 at 210 A cm −3 surpassing those of carbon, transition metal oxides/nitrides. Even the 150 μm-thick film electrode comprising VNNDs/CNSs has a volumetric capacitance of 867.1 F cm −3 . Moreover, the VNNDs/CNSs electrode exhibits extraordinary cycling stability with 90% capacitance retention after 10, 000 cycles. The all-solid-state symmetric flexible supercapacitor based on VNNDs/CNSs electrodes boasts a high volumetric energy density/power density of 30.9 Wh L −1 /64, 500 W L −1 with 91% capacitance retention after 10000 cycles, rendering promising applications in high-performance flexible supercapacitors. The strategy provides an insight into the rational design of compact, robust and highly conductive electrode materials with high volumetric capacitances and long life. Graphical abstract: fx1 Highlights: 0D-in-2D structured VN nanodots intercalated carbon nanosheets (VNNDs/CNSs). Spatially confined synthesis of VNNDs/CNSs via nitriding organic-inorganic hybrid PANI/V2 O5. VNNDs/CNSs show an ultrahigh volumetric capacitance of 1203.6 F cm −3 and long life. The VNNDs/CNSs electrode with 150 µm thickness has large volumetric capacitance.